Budaya Dan Praktik Manajemen Sumber Daya Manusia : (Studi Kasus Pada Perusahaan Pt. Suryagraha) - Nasya Soraya Yusuf; Muhammad Isa Anshori (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Corporate culture and Human Resource Management (HRM) practices are two inseparable elements that form the foundation of a successful organization . This article delves into two important dimensions of corporate culture and HR practices and explores how they are interrelated and impact overall corporate performance and identity. The research method in this research uses a qualitative approach , namely to get an overview of several cultures and practices that exist in the company The research techniques used are data collection, namely interviews, and observation. The data used in this study are primary data and secondary data. The results of this research are the culture and practice of HRM at PT. SURYA GRAHA plays a role in managing human resources and achieving company goals. and also he applies good and correct HR culture and practices so that they are relevant to research topics and help companies integrate HR culture and practices to improve their performance. Effective HR practices and a strong corporate culture are two inseparable elements in forming a developed organization. Both interact with each other and have an impact on the company's performance and identity . The Role of Culture in Performance, Corporate culture has a significant impact on employee behavior and organizational performance. A good culture can increase employee motivation, productivity, and awareness to improve their performance . Good HR practices such as selective recruitment, training, and development, can improve the quality of human resources in the organization.